1999
DOI: 10.1104/pp.121.3.1025
|View full text |Cite
|
Sign up to set email alerts
|

A Re-Evaluation of the Relative Roles of Two Invertases, INCW2 and IVR1, in Developing Maize Kernels and Other Tissues

Abstract: We have examined the relative abundance and distribution of the transcripts and protein products of a cell wall gene (Incw2) and a soluble invertase gene (Ivr1) to better understand their relative roles during maize (Zea mays L.) kernel development. In developing kernels the steady-state levels of Incw2 transcript increased dramatically from 0 to 12 d after pollination, while Ivr1 transcript, in contrast to a previous report, was undetectable. Consistent with the RNA expression data, the IVR1 protein could not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…The cell wall-bound invertase in the cell wall space can facilitate assimilate transfer from maternal tissues to the developing endosperm because lack of symplastic connections between these tissues necessitates an apoplastic cell wall step (Felker and Shannon, 1980). This is consistent with the suggestion that Incw2 is expressed primarily in filial cells (Carlson and Chourey, 1999). However, during early phases of growth, the kernel is almost entirely maternal tissue.…”
Section: Soluble Invertase and Hexose To Suc Balance In Young Ovariessupporting
confidence: 79%
See 2 more Smart Citations
“…The cell wall-bound invertase in the cell wall space can facilitate assimilate transfer from maternal tissues to the developing endosperm because lack of symplastic connections between these tissues necessitates an apoplastic cell wall step (Felker and Shannon, 1980). This is consistent with the suggestion that Incw2 is expressed primarily in filial cells (Carlson and Chourey, 1999). However, during early phases of growth, the kernel is almost entirely maternal tissue.…”
Section: Soluble Invertase and Hexose To Suc Balance In Young Ovariessupporting
confidence: 79%
“…7), together with contrasting developmental profiles for Ivr2 and Incw2 mRNA (Fig. 6), clearly support distinct temporal roles that were not readily resolvable by concurrent extraction of both enzymes in more mature kernels (Carlson and Chourey, 1999). The role of the Incw2 cell wall-bound invertase activity in Suc hydrolysis and assimilate transfer to developing endosperm at a later stage of kernel development has been detailed previously (Cheng et al, 1996).…”
Section: Soluble Invertase and Hexose To Suc Balance In Young Ovariesmentioning
confidence: 86%
See 1 more Smart Citation
“…Xu et al (1996) reported abundant levels of the two soluble invertases, Ivr1 and Ivr2, in developing kernels. However, subsequent analyses (Carlson and Chourey 1999;Anderson et al 2002;McLaughlin and Boyer 2004) report no Ivr1 expression in this tissue and the Ivr2 expression is predominantly localized in the maternal tissues, nucellus and pedicel, and is temporally restricted to the very early stages (up to the 8 DAP stage) of kernel development. A similar tissue profile of soluble invertase is also described in developing caryopsis of barley (Weschke et al 2003).…”
Section: Introductionmentioning
confidence: 93%
“…Thereafter, the membranes were blocked with 5% nonfat dry milk in PBS, pH 7.2, plus 0.1% Tween 20 and then probed for either cell wall invertase using polyclonal anti-maize INCW2 antibodies raised in mice (Carlson and Chourey, 1999) or for INVINH1 using antibodies raised in rabbit against a synthetic peptide of NNNLVETTC derived from the N terminus of INVINH1 (Mimotopes). Protein signals were detected using goat anti-mouse or anti-rabbit IgG conjugated with horseradish peroxidize for cell wall invertase and INVINH1, respectively, followed by visualization using a chemiluminescence system and densitometric quantification using the Image J program (http://rsb.info.nih.gov/ij/).…”
Section: Protein Gel Blot Analysesmentioning
confidence: 99%